L-carnitine supplementation in female infertility – is it working? - Laskus, Paulina; Przeradzki, Jakub; Rząd, Katarzyna; Borycka, Aleksandra; Kotulska, Maria; Potocka, Zofia; Lichman, Martyna; Lubczyńska, Zuzanna; Jędrzejewska, Barbara (Journal of Education, Health and Sport, 2023)
Introduction and objective: Infertility is estimated to affect around 15% of couples in reproductive age. Due to delayed decision about childbearing and unhealthy lifestyle it is increasing problem in many western countries. For that reason, people seek out supplements to enhance their fertility. L-carnitine is primarily known as a supplement often used by athletes to enhance exercise performance, but some reports suggest that L-carnitine may also have a positive effect on sperm and oocytes quality. The aim of this study was to summarize the published reports about L-carnitine impact on female fertility. Brief description of the state knowledge The primary mechanism of action of L-carnitine involves its role in the transport of long-chain fatty acids into the mitochondria of cells, where they are then metabolized in a process called beta-oxidation to produce energy. L-carnitine also have antioxidant properties, helping to protect cells from oxidative stress. It has also been suggested to play a role in modulating signaling pathways involved in metabolism, inflammation, and cellular growth and differentiation. Due to wide range of possible mechanisms of action L-carnitine is considered as a potential supplement for fertility. Summary The presented literature review suggests that L-carnitine has a promising effect on improving female fertility, especially when it comes to clomiphene citrate-resistant patients with polycystic ovary syndrome and in vitro fertilization. However, further studies are needed to confirm its role and exclude possible side effects of its use before it is routinely recommended for this indication.